The providing of youth's life quality in health promoting schools of L'viv region - Iuliia Pavlova; Olena Shyyan (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to establish the role of health-promoting schools in providing of life quality of youth of school age. Material & Methods: the project activity and its benefits for youth's life of 69 health promoting schools were analyzed. 2108 students of 10-11 grades was surveyed. 1080 students was studied in health promoting school. Results: the objective conditions for life quality formation according project activities 'Health promoting school' were described. The factors that contribute high life quality level of school youth were identified with regression analysis. Conclusions: the increasing of odds ratio for life quality was identified for males (in 2,2-2,6 times), for respondents with high levels of physical activity (in 1,3-2,8 times) and respondents which studied in health promoting schools (in 2,3-3,1 times).